PENGARUH TOTAL QUALITY MANAGEMENT (TQM) DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING - Melda Novia Saputri; Madani Hatta (JURNAL FAIRNESS, 2022)
This study aims to provide empirical evidence of the Effect of Total Quality Management (TQM) and Product Innovation on Competitive Advantage in the Convection and Printing business in Bengkulu City. The data used in this study are primary data, obtained by distributing questionnaires. The sample in this study was 37 convection and printing entrepreneurs in Bengkulu city who had opened a Convection and Printing business that had been operating for at least 5 years. The analysis technique uses the assistance of the SmartPLS 3.0 program. The results showed that Total Quality Management (TQM) contributes to Competitive Advantage and Product Innovation does not conflict with Competitive Advantage.